Optimization of CSG dam profile based on response surface methodology - Zelin Ding; Jianghan Xue; Xuanyi Zhu; Jing Wang (Case Studies in Construction Materials, 2022)
With the improvement of the construction technology of Cemented sand and gravel dam (CSG dam), it is necessary to design a safe and reasonable optimal profile to guide the subsequent construction of CSG dam. This paper selects the profile form of CSG dam as the research object, and uses the response surface method to carry out weight optimization analysis on the three factors of dam height, slope ratio, and cemented material content. The optimal profile forms of CSG dam under different dam heights and cemented materials are calculated using least square method. Finally, the optimized profile form is selected and compared with the Shoukoubao dam in Shanxi Province by the model test. The models go through the elastic stage until the plastic stage fails. Compared with the actual engineering model, the maximum strain of the optimized section model is reduced by 20.57 %, the maximum displacement value is reduced by 8.92 %, and the overload safety degree is enhanced by 5.88 %. The results provide a scientific basis for the optimization of the profile form of the CSG dam in the actual project, and provide a simple and reliable method for constructing the CSG dam in the future.